Hubungan Minat dan Kemandirian dengan Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 8 Palangka Raya - Ganefi, Septi; Sugiharto, Sugiharto; Friantini, Rizki Nurhana (JURNAL PENDIDIKAN, 2026)
This research is motivated by the low learning outcomes of students, the lack of interest in learning mathematics, and the lack of independence in learning mathematics. The objectives of this research are to determine: 1) the positive relationship between learning interest and mathematics learning outcomes, 2) the positive relationship between learning independence and mathematics learning outcomes, 3) the positive relationship between interest and independence and mathematics learning outcomes. This research uses a quantitative approach with a correlational research type. The population in this study were 363 students of class VIII of SMP Negeri 8 Palangka Raya and the research sample consisted of 208 students. The analysis requirement test, namely the data normality test with Kolmogorov-Smirnov, obtained three data with normal distribution. From the results of the hypothesis test, it shows that: (1) there is a significant positive relationship between learning interest and students’ mathematics learning outcomes, the correlation coefficient is , the significance test is ; (2) there is a significant positive relationship between learning independence and students’ mathematics learning outcomes, the correlation coefficient is , the significance test is ; (3) there is a significant positive relationship between learning interest and independence with students’ mathematics learning outcomes, the correlation coefficient is , the significance test is . The results of this study are expected to contribute to the development of learning theory in the field of mathematics education, especially those related to internal factors in students mathematics learning outcomes, such as learning interest and learning independence.